Australian Government's Public Diplomacy through the MAMPU Program in Indonesia (2016-2020) - Haerani Destiningrum; Elvianti, Witri (Jurnal Hubungan Internasional, 2023)
This paper discusses the Australian government's public diplomacy effort through the MAMPU program phase II (2016 - 2020) which focuses on gender equality and women's empowerment issues in Indonesia. The author used the concept of public diplomacy in this paper to analyse what the Australian government has done to achieve its interest through the MAMPU program. The paper uses a qualitative method with a descriptive approach, by using secondary and primary data which are program MAMPU's social media, website, various documents, entries from the internet, and an interview with MAMPU Program Manager from BaKTI Foundation. This paper finds that efforts conducted by the Australian government in the MAMPU program are compatible with four of the five relational initiatives characteristics in public diplomacy. Furthermore, because of its public diplomacy through the MAMPU program, the Australian government gained positive images as a country that supports the women empowerment issue in Indonesia. In addition, the Australian government could also strengthen its relationship with the Indonesian government.